PENGARUH PENGEMBANGAN KARIER DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KESEHATAN KOTA PALEMBANG - Martinawati, Lusi (MOTIVASI, 2017)
Purpose - This research is intended to find out the influence of Career Development and Motivation, by together to Official Performance, and then Influence of Career Development and Motivation, by partial to Official Performance.Â  Design/methodology - Population in this research as much 100 people On Public Health Service of Palembang Town. From calculation result by using program of SPSS for Windows Version 16.00, got result that 1) There is influence of Career Development and Motivation which significant by together To Official Performance; 2) There is influence of Career Development which significant by partial To Official Performance; and 3) The is influence of Motivation which significant by partial To Official Performance. Findings â€“ Implementation in this research, can see the theory application and its result, what is used to assist The Public Health Service of Palembang Town; to repairing existing Official Performance.